The Diagnostic Accuracy of Novel Biomarkers Anti-ApoA-1, Anti-MDA-LDL, and Anti-Osteopontin IgG for Detecting Silent Myocardial Ischemia: Novel Biomarkers Anti-ApoA-1, Anti-MDA-LDL, and Anti-Osteopontin IgG in Myocardial Ischemia - Wang, Zhongqing; Sun, Bin; Wang, Wei; Xiong, Tinglin; Wei, Gang (Journal of Medical Biochemistry, 2026)
Background: Silent myocardial ischemia (SMI) is a significant predictor of adverse cardiac events but remains underdiagnosed. We evaluated the diagnostic accuracy of three autoimmune-inflammation linked biomarkers—anti-apolipoprotein A-1 (anti-ApoA-1) IgG, anti-malondialdehyde-modified low-density lipoprotein (anti-MDA-LDL) IgG, and anti-osteopontin (anti-OPN) IgG—for detecting SMI.Methods: In this cross-sectional study, 210 participants were categorized into three groups: SMI (n=70), stable angina (SA, n=70), and healthy controls (n=70). SMI was defined by exercise-induced ST-segment depression on treadmill testing without symptoms. Serum levels of the three antibodies were measured by enzyme-linked immunosorbent assay. Receiver operating characteristic (ROC) analysis determined the area under the curve (AUC), sensitivity, and specificity.Results: All three biomarkers were significantly higher in the SMI group compared to SA and controls (p
Keywords: Silent Myocardial Ischemia; Autoantibodies; Apolipoprotein A-I; Malondialdehyde-Modified Low-Density Lipoprotein; Osteopontin; Biomarkers; Diagnostic Accuracy; Coronary Artery Disease; Atherosclerosis; Enzyme-Linked Immunosorbent Assay